Cockroach allergy in a group of Turkish children with respiratory allergies - Yılmaz, Aygen; Tuncer, Ayfer; Şekerel, Bülent E.; Adalıoğlu, Gönül; Saraçlar, Yıldız (The Turkish Journal of Pediatrics, 2004)
Exposure to cockroach may lead to exacerbations of bronchial asthma and/or allergic rhinitis in sensitized patients. Although there is a widespread belief that cockroach allergy is a common problem in patients with respiratory allergies, little is known in Turkish children. In order to investigate the prevalence and characteristics of cockroach allergy in respiratory allergic children, we performed a study in newly referred children with respiratory allergies. All patients underwent questionnaire-interview and skin prick tested with common inhalant allergens in addition to two cockroach allergens: Blatella germanica (Bg) and Periplaneta americana (Pa). A subgroup of patients was also serologically investigated for specific IgE against Bg and house dust mite. Three hundred- and thirty-seven children aged 2-16 years were recruited for the study and 77.7% of these were atopic, with the most common indoor and outdoor allergens of house dust mite (47.5%) and grass pollens (45.1%), respectively. According to the prick test results, allergies to Bg and Pa were 11.9% and 7.4%, respectively, and there was a weak correlation between size of the prick test and specific IgE levels for Bg allergen. Almost 30% of the cockroach-sensitive patients were allergic to both cockroach antigens. Seventy percent of cockroach-sensitive patients were also sensitive to house dust mite, and only 1% were monosensitive. Dwellings in the Middle Anatolia and Black Sea regions were less commonly infested by cockroach compared to the dwellings in other regions. In conclusion, our preliminary study showed that cockroach sensitization is common among children with respiratory allergies irrespective of infestation history, suggesting that addition of cockroach allergen to the routine allergy screening panel is critical.